Effect of FGFR inhibitors on chicken limb development - Horakova, Dana; Cela, Petra; Krejci, Pavel; Balek, Lukas; Moravcová Balková, Simona; Matalova, Eva; Buchtová, Marcela (Development growth & differentiation, 2014)
Fibroblast growth factor (FGF) signalling appears essential for the regulation of limb development, but a full complexity of this regulation remains unclear. Here, we addressed the effect of three different chemical inhibitors of FGF receptor tyrosine kinases (FGFR) on growth and patterning of the chicken wings. The inhibitor PD173074 caused shorter and thinner wing when using lower concentration. Microinjection of higher PD173074 concentrations (25 and 50 mmol/L) into the wing bud at stage 20 resulted in the development of small wing rudiment or the total absence of the wing. Skeletal analysis revealed the absence of the radius but not ulna, deformation of metacarpal bones and/or a reduction of digits. Treatment with PD161570 resembled the effects of PD173074. NF449 induced shortening and deformation of the developing wing with reduced autopodium. These malformed embryos mostly died at the stage HH25-29. PD173074 reduced chondrogenesis also in the limb micromass cultures together with early inhibition of cartilaginous nodule formation, evidenced by lack of sulphated proteoglycan and peanut agglutinin expression. The effect of FGFR inhibition on limb development observed here was unlikely mediated by excessive cell death as none of the inhibitors caused massive apoptosis at low concentrations. More probably, FGFR inhibition decreased both the proliferation and adhesion of mesenchymal chondroprogenitors. We conclude that FGFR signalling contributes to the regulation of the anterior-posterior patterning of zeugopod during chicken limb development.
Keywords: kuřecí embryo; receptory fibroblastových růstových faktorů; Benzenesulfonates; Animals; benzensulfonáty; pyrimidiny; inhibitory proteinkinas; Pyrimidines; Signal Transduction; signální transdukce; Wings, Animal; Receptors, Fibroblast Growth Factor; křídla zvířecí; Chick Embryo; Protein Kinase Inhibitors; zvířata